Climate change projections for the surface ocean around New Zealand - Cliff S. Law; Graham J. Rickard; Sara E. Mikaloff‐Fletcher; Matt H. Pinkerton; Erik Behrens; Steve M. Chiswell; Kim Currie (New Zealand Journal of Marine and Freshwater Research, 2018)
The future status of the surface ocean around New Zealand was projected using two Earth System Models and four emission scenarios. By 2100 mean changes are largest under Representative Concentration Pathway 8.5 (RCP8.5), with a +2.5°C increase in sea surface temperature, and decreases in surface mixed layer depth (15%), macronutrients (7.5–20%), primary production (4.5%) and particle flux (12%). Largest macronutrient declines occur in the eastern Chatham Rise and subantarctic waters to the south, whereas dissolved iron increases in subtropical waters. Surface pH projections, validated against subantarctic time‐series data, indicate a 0.335 decline to ∼7.77 by 2100. However, projected pH is sensitive to future CO 2 emissions, remaining within the current range under RCP2.6, but decreasing below it by 2040 with all other scenarios. Sub‐regions vulnerable to climate change include the Chatham Rise, polar waters south of 50°S, and subtropical waters north of New Zealand, whereas the central Tasman Sea is least affected.